2011
DOI: 10.1057/jphp.2011.33
|View full text |Cite
|
Sign up to set email alerts
|

Research in support of health systems transformation in South Africa: The experience of the Centre for Health Policy

Abstract: We describe the role and experience of the Centre for Health Policy (CHP), a university-based research unit established in 1987, in influencing and supporting health systems transformation in South Africa over two decades. During 2010, we analyzed relevant documents and conducted interviews with 25 key informants. CHP's research has contributed directly to health policy development and implementation while also changing the way government understood or approached policy issues. Key success factors for policy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 13 publications
1
34
0
Order By: Relevance
“…In line with previous research [5,6,19-24], we found that a range of contextual factors were critical in facilitating the use of the survey findings. In particular, the 2002 NSW Child Obesity Summit [18] provided a supportive policy context which facilitated the formation of partnerships between survey researchers and EUs, and provided mechanisms and structures (such as the NSW Government Action Plan for Child Obesity Prevention 2003–2007, [16] and a Senior Officers Group with responsibility for overseeing implementation of this plan) which facilitated application of survey findings.…”
Section: Discussionsupporting
confidence: 89%
“…In line with previous research [5,6,19-24], we found that a range of contextual factors were critical in facilitating the use of the survey findings. In particular, the 2002 NSW Child Obesity Summit [18] provided a supportive policy context which facilitated the formation of partnerships between survey researchers and EUs, and provided mechanisms and structures (such as the NSW Government Action Plan for Child Obesity Prevention 2003–2007, [16] and a Senior Officers Group with responsibility for overseeing implementation of this plan) which facilitated application of survey findings.…”
Section: Discussionsupporting
confidence: 89%
“…There are several recognised difficulties in attributing a policy impact to a specific piece of research [ 5 , 69 , 70 ]. The original piece of research may be re-interpreted in the policy process in ways that are incorrect or not consistent with its intent, or it may be adapted to particular contexts and transformed in the process.…”
Section: Discussionmentioning
confidence: 99%
“…The rising importance of HPSR+A reflects the need for adequate research and analytical capacity in a range of organizations including ministries of health, health policy analysis institutes, think tanks, academia and civil society ( Green and Bennett 2007 ; Mayhew et al 2008 ; Ranson and Bennett 2009 ; Greer 2010 ; Omaswa and Boufford 2010 ; Bennett et al 2012b ; Rispel and Doherty 2011 ).…”
Section: Introductionmentioning
confidence: 99%